Hierarchical Markov model used in the reliability assessment and management of low-voltage switchgear. (September 2017) - Wang, Jingqin; Wang, Li; Wang, Ching-Hsin; Zhang, Zhigang
In this article, the reliability assessment and management of low-voltage switchgear was introduced based on a hierarchical Markov model. First, the reliability block diagram of motor control center was established by actual circuit. The low-voltage switchgear was divided into modules by different functions of reliability block diagram to build the hierarchical structure model which contained five layers. The first and the second layers were low-voltage switchgears and modules, helpful to identify key modules. The others were units and components, essential to establish the reduced model. Therefore, the state transition diagrams of layers were plotted and the transition density matrixes of layers were given easily. Steady-state equations of each layer were constructed and solved to obtain the availability and steady-state probabilities of modules and components. Next, the reliability assessment and management of GCK4 low-voltage drawer-type switch cabinet motor control center was presented. Finally, critical components and critical modules were found, but their running state in the management process should be carefully monitored. The hierarchical Markov model realizes a rapid and convenient analysis of system reliability. The results provide theoretical support for identifying key module and component and developing rational maintenance and management strategy for low-voltage switchgear and other repairable complex systems.